The Aggressiveness of Russia’s Politic and the Limitations of Western Europe’s Politic - Choy, Looi Theam (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2020)
The purpose of this topic is to discuss the massive limitations of Pro-Western policies based on the impacts of Ukraine crisis and Crimea annexation. The international orders that existed nowadays, such as the UN Charter, NATO Articles, and EU policies, are purposely set-up to promote global peace and harmony in our world order. However, the impact of the Ukraine crisis is contrary to the intention of international orders, as the reality in Europe. The scope of this study is restricted to the NATO policies, EU policies, and the introduction of the UN Charter. Content analysis is the methodology to identify three sections for this study. This study is divided into three sections, i.e. the limitation of the Western policy in the Ukraine conflict, the weakness of NATO military power, and the failure of Pro-Western policies in the case of Ukraine crisis. The sections were analysed by the Neoclassical realism approach to ascertain the irrelevance of the international orders within the parameters of the UN Charter, NATO Articles, and EU policies. Limitations of Pro-Western policies in the case of the Ukraine crisis is unprecedented for the application of Neoclassical realism; hence, reasonably understanding the situation of the Ukraine crisis is the primary application of this study.